Loss of vhl in the zebrafish pronephros recapitulates early stages of human clear cell renal cell carcinoma - Haley R. Noonan; Ana M. Metelo; Caramai N. Kamei; Randall T. Peterson; Iain A. Drummond; Othon Iliopoulos (The Company of Biologists, 2016)
Patients with von Hippel-Lindau (VHL) disease harbor a germline mutation in the VHL gene leading to the development of several tumor types including clear cell renal cell carcinoma (ccRCC). In addition, the VHL gene is inactivated in over 90% of sporadic ccRCC cases. 'Clear cell' tumors contain large, proliferating cells with 'clear cytoplasm', and a reduced number of cilia. VHL inactivation leads to the stabilization of hypoxia inducible factors 1a and 2a [HIF1a and HIF2a (HIF2a is also known as EPAS1)] with consequent up-regulation of specific target genes involved in cell proliferation, angiogenesis and erythropoiesis. A zebrafish model with a homozygous inactivation in the VHL gene (vhl−/−) recapitulates several aspects of the human disease, including development of highly vascular lesions in the brain and the retina and erythrocytosis. Here, we characterize for the first time the epithelial abnormalities present in the kidney of the vhl−/− zebrafish larvae as a first step in building a model of ccRCC in zebrafish. Our data show that the vhl−/− zebrafish kidney is characterized by an increased tubule diameter, disorganized cilia, the dramatic formation of cytoplasmic lipid vesicles, glycogen accumulation, aberrant cell proliferation and abnormal apoptosis. This phenotype of the vhl−/− pronephros is reminiscent of clear cell histology, indicating that the vhl−/− mutant zebrafish might serve as a model of early stage RCC. Treatment of vhl−/− zebrafish embryos with a small-molecule HIF2a inhibitor rescued the pronephric abnormalities, underscoring the value of the zebrafish model in drug discovery for treatment of VHL disease and ccRCC.